Dose-Dependent Effects of Turmeric (Curcuma aromatica S.) Starch on Colonic Fermentation in Rats - Ekanayake, Ekanayake Mudiyanselage Asanka Chamara; Ishii, Ryota; Nagata, Ryuji; Shimada, Ken-ichiro; Han, Kyu-Ho; Fukushima, Michihiro (Metabolites, 2024)
Background; Turmeric starch (TS) has gained significant attention due to its potential health benefits. Rich in resistant starch (RS) and higher in phosphorus, TS is anticipated to possess properties of high-phosphorus-type RS. Objectives; To understand the host physiology of TS, this study investigated the dose-dependent effects of TS on colonic fermentation in rats. Methods; Four experimental diets containing different levels of TS (5%, 10%, and 20% w/w) were formulated and fed to male Fischer 344 rats for two weeks and compared with rats fed a 0% TS diet (TS0). Results; Results showed that increasing the dose of TS resulted in reduced body weight gain, lower visceral tissue weight, and increased cecal mucin and IgA levels compared with the TS0 group. Further, fecal dry weight increased dose-dependently parallel to the starch excretion rate. Higher doses of TS resulted in increased short chain fatty acid (SCFA) production, specifically cecal acetate content, as well as in a dose-dependent decrease in the cecal pH level. However, this study did not observe a positive effect of TS on colonic alkaline phosphatase (ALP) activity, and the impact on small intestinal ALP activity remains unclear. Notably, beneficial bacteria such as the family Oscillospiraceae, genus Lachnospiraceae NK4A136 group, and Ruminococcus spp. were found to have been enriched in the TS-fed groups, further supporting the beneficial effects of TS on gut microbiota and SCFA production. Additionally, the genus Mucispirillum, which is known to possess beneficial and opportunistic pathogenic traits under immunocompromised states, was found in the TS-fed groups. Conclusions; According to these results, it is clear that TS served as a prebiotic substrate in rats, with a notable modulation of the microbial composition.